A generalized integrated population model to estimate greater sage‐grouse population dynamics - Rebecca McCaffery (Ecosphere, 2016)
Abstract For species of conservation concern, assessing population dynamics consistently across different populations is of paramount importance to effective conservation and restoration planning. This effort presents a challenge for wide‐ranging species with considerable variation in both abundance and demographic rates. Raw counts of individuals are typically used to assess population trends at broad scales, but the demographic rates that explain changes in population size can only feasibly be measured at local scales. We developed a generalized integrated population model, which combines the strengths of these two data types, for the greater sage‐grouse (Centrocercus urophasianus). We used N‐mixture models to estimate annual abundance from counts of males at breeding leks and constructed a two‐sex, demographic matrix model using published vital rate estimates for male and female sage‐grouse from across their range. We applied the model to 13 years of statewide lek counts for Montana, USA. Then, we applied the model to local, annually varying vital rate estimates and lek count data from a population in the Powder River Basin in Montana and Wyoming. We demonstrate potential for this modeling approach to improve our understanding of sage‐grouse population dynamics in a consistent and robust framework, especially as data quality and quantity increases. We use our results to highlight the need for better data on sex and age ratios, female population size, and the proportion of active leks being monitored each year. While our model was focused on the greater sage‐grouse, this approach could be applied to a variety of sensitive species to compare population dynamics across a species’ range.